New growth references for assessment of stature and skeletal maturation in Australians - Lin Ni-Hung; Ranjitkar Sarbin; Macdonald Ross; Hughes Toby; Taylor Jane A.; Townsend Grant C. (Sciendo, 2023)
We have provided evidence of secular increases in stature and acceleration of skeletal maturation in Australian male children and young adults in recent decades, and relatively less prominent secular increases in stature in females.